Estudo comparativo dos métodos ABCP e IPT modificado para dosagem de concreto de cimento portland - Freitas, Paulo Natã Lopes de (Universidade Federal Rural do Semi-Árido, 2018)
There are different types of work paths that can be useful in construction, and those that are already used can have several advantages for a building site. Both in the resistance and productivity, and in the final cost of production. The dosage methods were used in ABCP and IPT / Modified. Where the IPT / Modified was made more economical than the ABCP at 7.67%. Decreasing the most expensive item of concrete, which is cement.
Monografia
Keywords: IPT; Métodos de dosagem; Concreto; ABCP; IPT; Dosage methods; Concrete; ABCP; ENGENHARIAS::ENGENHARIA CIVIL